Determinants of retirement planning decision among employees in Petronas Carigali Sdn Bhd / Siti Nurhafiza Mohd Salleh and Sharil Azam Mohd Isa - Mohd Salleh, Siti Nurhafiza; Mohd Isa, Sharil Azam (2014)
During the past several decades, individuals have been asked to shoulder an increasing portion of the burden of the financial preparation for their retirement. Employers have shifted emphasis away from plans that promise retired employees a certain income for life to plans where value at retirement depends on employee investment decisions and market fluctuations. In this changing planning environment, tax-sheltered retirement savings vehicles such as individual retirement accounts (IRAs), Keogh plans for the self-employed, 401(k), 403(b), thrift plans, and supplemental retirement annuities have gained importance in retirement plans. These plans allow an employee to decide whether or not to participate, and to decide, within certain limits, how much to contribute to the plan. With these plans, the employee becomes a much more active decision maker in the retirement planning process and the level of living achieved during retirement will depend on the decisions made. There is some evidence that debt obligations may be keeping employees from taking full advantage of such plans, possibly compromising their opportunities for achieving a desirable level of living during retirement. In a recent survey of investors, over one in 10 respondents stated that high levels of non-mortgage debt prevented them from contributing to their 401(k) plan. Thirty-five percent indicated that debt prevented them from contributing as much as they would like (Gunsauley, 2000). Given the importance of discretionary savings for retirement, it is of interest to explore the extent to which this situation represents a prevalent problem in the United States. This study uses nationally representative data to examine the relationship between debt levels and participation in and level of discretionary retirement savings. Therefore, the purpose of this study is to examine the determinants that affect the retirement planning decision among employees in PETRONAS Carigali Sdn Bhd. The multiple linear regressions are used in this study to assess the relationship between the dependent variable (retirement planning decision) and independent variable (unforeseen medical expenses, daily expenses, investment and debt). The result of this study shows there is two determinants that significantly related to the retirement planning decision which is unforeseen medical expenses and increasing cost of living